Penerapan pendidikan nilai perpaduan dalam kalangan murid sekolah menengah melalui novel komponen sastera - Husairi, Hussin (2021)
Malaysia consists of multi-ethnicity society. The ethnic diversity may occasionally instigate sames dissatisfaction among these distinct ethnic groups which may eventually affect the country's unity. Through the teaching and learning process of Malay Literature component (KOMSAS), the aspect of unity may be instilled. The main aim of this research is to analyze the values of unity in KOMSAS novels for KSSM. Secondly, this study also discusses the manners in which the value of unity in KOMSAS are instilled in students. Next, it also describes the effectiveness of inculcating the value of unity through KOMSAS novels. This study uses qualitative research approach as its research design. A content analysis used to analyze eight KOMSAS novels for KSSM and a thematic analysis based on Lukacs Reflection Theory is employed to discuss the findings of the study. The findings indicated that the selected KOMSAS novels had discussed the values of unity namely openmindedness, thrustworthiness, fairness based on KSSM accordingly. Next, the findings indicated that the authors had applied two approaches namely the use of dialogues and descriptive writing in their efforts to implant the value of unity in their literary work. It is obvious that the process of instilling the value of unity in students through KOMSAS novels is suitable because it is community-friendly. Due to this, students are able to practice this value in their daily life. The study has provided some significant implications in terms of the implementation of KOMSAS in teaching Malay Language. KOMSAS had helped to inculcate the value of unity in students. Hence, educators should be wise in managing the teaching and learning process so that the students can cherish the value of unity in KOMSAS novels.